Teacher Assignment Management Based on Competencies and Academic Qualifications in the Perspective of Islamic Education - Rahayu Mardikaningsih; Muhammad Ainul Misbah Alfarid; Partono; Mila Hariani; Didit Darmawan (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Human resource management in schools determines the effectiveness of the learning process, one of which is through the distribution of teaching tasks. Placing teachers who do not align with their educational background and expertise can reduce the quality of teaching and organizational performance. This study aims to examine the ideal distribution of teaching tasks based on teacher competency and qualifications. The method used is a literature review analyzing various relevant educational management concepts and theories. The results of the study indicate that effective distribution of tasks must be based on appropriate disciplines, mastery of professional and pedagogical competencies, and a proportional workload analysis. Implementing this principle requires accurate data support, policy transparency, and active teacher participation. The implications of these findings emphasize the importance of careful planning and a continuous evaluation system to ensure that each task is assigned to the most appropriate personnel, thereby improving the quality of learning and overall school performance.